The Function of Directive Speech Acts in Gamal Komandoko's Indonesian Archipelago Folklore Text (Universitas Negeri Semarang, 2018)
The directive speech acts have many functions. The functions of the directive speech acts include: forcing, inviting, asking, ordering, charging, urging, begging, advising, suggesting, commanding, giving cues, challenging. Folklore text is chosen as the data source due to it contains the utterances used by the characters to interact. The purposes of this research are to describe the function of directive speech acts in Indonesian archipelago folklore text written by Gamal Komandoko and to determine which function of directive speech act is dominant in Indonesian archipelago text written by Gamal Komandoko. The data are collected using observation method and writing technique. The data are analyzed using pragmatic analysis. The results of this study show some functions of directive speech. They are (1) requesting: 7 speeches, (2) begging: 5 speeches, (3) suggesting: 8 speeches, (4) commanding: 6 speeches, (5) ordering: 18 speeches, (6) advising: 1 speech, (7) forcing: 2 speeches, (8) inviting: 4 speeches, (9) prohibiting: 1 speech, (10) challenging: 4 speeches, (11) proposing: 1 speech, (12) giving cues 1 speech. The total of directive speech acts function data in Gamal Komandoko's Indonesian archipelago text are 58 utterances. The dominant function found in the text is the ordering function. This research is expected to be useful for pragmatic studies especially in speech acts.